Association between the number of sexual partners and alcohol consumption among schoolchildren - Rachel Mola; Rodrigo C. Araújo; Jéssica Vanessa B. Oliveira; Samara B. Cunha; Gabriely F.F. Souza; Luanda P. Ribeiro; Ana Carolina R. Pitangui (Brazilian Society of Pediatrics, 2017)
Objective: To determine the association between the number of sexual partners and alcohol consumption in adolescents and young schoolchildren. Methods: The sample consisted of students from public schools aged 12-24 years who answered the Brazilian version of the Youth Risk Behavior Survey questionnaire. The analysis was performed by multinomial logistic regression model. Results: 1275 students were analyzed. For females, having two to five partners was associated with age ≥15 years (OR 14.58) and maternal education up to incomplete high school or lower educational level (OR 3.37). No consumption of alcohol decreased the chances of having more partners by 96%. For males, the associated variables were: age ≥15 years (OR 18.15); having no religion (OR 3.55); age at first dose ≤14 years (OR 3.48). Binge drinking increases the chances of having a higher number of sexual partners. Conclusion: Regardless of the number of partners, binge drinking and age of alcohol consumption onset are risk factors for vulnerable sexual behavior.